2022
DOI: 10.3389/fmicb.2022.806398
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis Across 128 Phytophthora Isolates Reveal Species-Specific Microsatellite Distribution and Localized Evolution of Compartmentalized Genomes

Abstract: Phytophthora sp. are invasive groups of pathogens belonging to class Oomycetes. In order to contain and control them, a deep knowledge of their biology and infection strategy is imperative. With the availability of large-scale sequencing data, it has been possible to look directly into their genetic material and understand the strategies adopted by them for becoming successful pathogens. Here, we have studied the genomes of 128 Phytophthora species available publicly with reasonable quality. Our analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…It is often accepted that larger genomes harbor more SSRs than smaller ones; although, there is no clear association between SSR content and genome size [ 79 , 80 , 81 ]. This statement does not seem proper for fungi, as several fungal species have varying SSR frequencies and abundances in their genomes, despite having equivalent genome sizes [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is often accepted that larger genomes harbor more SSRs than smaller ones; although, there is no clear association between SSR content and genome size [ 79 , 80 , 81 ]. This statement does not seem proper for fungi, as several fungal species have varying SSR frequencies and abundances in their genomes, despite having equivalent genome sizes [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effector genes are enriched in these specific genomic compartments (Dong et al., 2015 ; Raffaele & Kamoun, 2012 ). A recent report describing 128 Phytophthora species revealed that, apart from effectors, many other virulence genes encoding carbohydrate‐active enzymes (CAZymes), transcriptional regulators, signal transduction genes, ATP‐binding cassette transporters, and ubiquitins are also present in the repeat‐rich compartments (Mandal et al., 2022 ). Effector genes display expression polymorphisms, and the growing body of evidence suggests that these gene expression polymorphisms contribute to microbial responses to environmental challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many Phytophthora species have developed resistance to numerous compounds we use to control them. An abundance of transposable elements, mobile genetic elements, have facilitated the large expansion of many Phytophthora genomes (Gijzen, 2009;Mandal et al, 2022;Raffaele & Kamoun, 2012;Tyler et al, 2006). This has resulted in the duplication and evolution of many effector proteins (involved in virulence and pathogenicity) and detoxification enzymes that increase resistance to fungicides (Mandal et al, 2022;Tyler et al, 2006;.…”
Section: Development Of Resistancementioning
confidence: 99%